Uptake and bioaccumulation of nanoparticles by five higher plants using single-particle-inductively coupled plasma-mass spectrometry. Issue 8 (20th July 2022) - Wang, Jing; Yue, Le; Zhao, Jian; Cao, Xuesong; Wang, Chuanxi; Chen, Feiran; Xiao, Zhenggao; Feng, Yan; Wang, Zhenyu
Abstract : The exposure risk of nano-enabled products towards plants and related food safety. Abstract : The exposure risk of nano-enabled products towards plants and related food safety has attracted great attention. Here, particle concentrations and the size distribution of nanoparticles (NPs) in five plants (rice, maize, cucumber, amaranth and kidney bean) after foliar exposure to CeO2, La2 O3, Fe3 O4, and MnFe2 O4 NPs at a concentration of 10 mg L −1 were quantified by single-particle-inductively coupled plasma-mass spectrometry (SP-ICP-MS). All four NPs were taken up by the five plants. In the dosed leaves (application site) of the five plants, the mean sizes of Ce- and La-based NPs were 30–39 nm and 20–55 nm, respectively, close to their original sizes. The mean sizes of Fe-based NPs (Fe3 O4 and MnFe2 O4 ) were in the range of 170–185 nm and 119–166 nm, respectively, larger than their original sizes. After transport to the leaves and roots, Ce-, La- and Fe (MnFe2 O4 )-based NPs had smaller mean sizes than those in the dosed leaves, while Fe (Fe3 O4 )-based NPs had a larger size. The particle concentrations of Ce-, La- and Fe (Fe3 O4 )-based NPs in amaranth dosed leaves were higher than those in other plants, by up to 6 times, and the concentration of Fe (MnFe2 O4 )-based NPs (9.78 × 10 6 particles L −1 ) was the highest in kidney beans compared to the other plants. The quantification of NPs in amaranth leaves after in vitro -simulated gastro and gastrointestinal digestion further revealed that all four NPs were possibly accessible to the human system, ranging from 5–79%. This study provides significant guidance for the assessment of the bioaccumulation of NPs in plants and their environmental health risks.